Spontaneous Pneumomediastinum and Diffuse Subcutaneous Emphysema after Methamphetamine Inhalation - Agustin, Michael (Case Rep Pulmonol, 2020)
Methamphetamines are commonly abused drugs for their stimulant and euphoric effects. Inhaled and intravenous use may cause damage to the respiratory system. Spontaneous pneumomediastinum is a condition where changes in intrathoracic pressure leads to alveolar rupture and dissection of air along the tracheobronchial tree. Massive subcutaneous emphysema may result from pneumomediastinum which may compromise the central airway. In this case report, we present an unusual case of spontaneous pneumomediastinum and severe subcutaneous emphysema following inhalation of methamphetamine. This case emphasizes the rising concern on the acute respiratory complications of methamphetamine use.